2018
DOI: 10.31487/j.scr.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A case of Zinner’s syndrome (seminal vesicle cyst with ipsilateral renal agenesis) presenting antenatally

Abstract: We present a case of a male infant with right renal agenesis associated with an ipsilateral cystic abnormality of the seminal vesicle, also known as Zinner's syndrome. The infant presented with renal agenesis antenatally at the 20-week gestation anomaly scan, with the cystic seminal vesicle being identified postnatally. We suggest, therefore, that the absent kidney in Zinner's syndrome is a true congenital abnormality rather than a postnatal involution of a dysplastic kidney as has been previously argued by so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, only 5 cases had been published to date in the literature. [8][9][10][11][12] It was reported that perhaps the occurrence of these two abnormalities was incidental. 9 The unique feature of our case was that the presenting disorder was resistant hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only 5 cases had been published to date in the literature. [8][9][10][11][12] It was reported that perhaps the occurrence of these two abnormalities was incidental. 9 The unique feature of our case was that the presenting disorder was resistant hypertension.…”
Section: Discussionmentioning
confidence: 99%